Christian involvement in Sustainable Development Goals - Raymond Downing (Health for All Nations, 2016)
The Sustainable Development Goals are the latest means to attempt to attain health for all as an end. This article examines this means from a Biblical perspective, asking Christians to examine not only the means we use to achieve ends, but more profoundly the way we determine what our ends are.